PROBLEMS OF THE CONCEPT IN THE LINGUISTICS (Web of Teachers: Inderscience Research, 2026)
This article devotes to learn concept, it’s meaning, structure and mental representation. Concepts are defined as abstract ideas or general notions that occur in the mind, in speech, or in thought. They are understood to be the fundamental building blocks of thoughts and beliefs. They play an important role in all aspects of cognition. As such, concepts are studied by several disciplines, such as linguistics, psychology, and philosophy, and these disciplines are interested in the logical and psychological structure of concepts, and how they are put together to form thoughts and sentences. The study of concepts has served as an important of an emerging interdisciplinary approach called cognitive science.